Speech of Mark Van Doren - Van Doren, Mark, 1894-1972.
Signed reading copy of a speech entitled, "Lincoln and Sandburg," made by Van Doren at the tribute to Carl Sandburg at the Lincoln Memorial, Washington, D.C., September 17, 1967, following Sandburg's death in July of that year.
Author, poet, and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865.; Sandburg, Carl, -- 1878-1967 -- Death and burial; Eulogies; Lincoln Memorial (Washington, D.C.); Memorial rites and ceremonies -- Washington (D.C.); Authors; Educators; Poets